Distribution of Bupivacaine after Interpleural Injection in Rats. Issue 1 (January 1991) - Strömskag, K. E.; Minor, B. G.; Post, C.
Abstract : The absorption and distribution of bupivacaine in several tissues was studied after interpleural injection of 14 C-labelled bupivacaine through a small needle interpleurally on the right side in male rats. 14 C-labelled bupivacaine 10 μCi /mmol was injected at a dose of 2.5 mg/kg. The animals, a total of 42, six at each testing time, were sacrificed at 5, 10, 20, 30, 60, 120 and 180 minutes after the interpleural injection. Bupivacaine concentration was then determined on the basis of the amount of radioactivity in tissues taken from 23 different locations. The highest concentration of bupivacaine, about 40 pmol/μg tissue, was found in the right lung in the middle and inferior lobes. In the inferior and dorsal aspects of the right thoracic wall, the concentrations were in the same range. In the more peripheral organs, such as the musculature in the legs, the concentration was as low as less than 5 pmol/μg. In the central nervous system, the concentration was less than 10 pmol/μg. Our conclusion is that interpleurally administered bupivacaine remains in the area of injection for a considerable time.